1980
DOI: 10.1071/bi9800479
|View full text |Cite
|
Sign up to set email alerts
|

An Electrophoretically Cryptic Alcohol Dehydrogenase Variant in Drosophila Melanogaster. I. Activity Ratios, Thermostability, Genetic Localization and Comparison With Two Other Thermostable Variants

Abstract: The alcohol dehydrogenase (ADH) variant ADH-FCh.D. has a secondary alcohol/primary alcohol activity ratio characteristic of ADH-S although it has an electrophoretic mobility inseparable from ADH-F. ADH-FCh.D. is distinguished from these two common ADH variants by being much more thermostable.Genetic analysis suggests that ADH-FCh.D. is specified by an allele at the Adh locus. Biochemical comparisons show that ADH-FCh.D. has the same electrophoretic mobility, activity ratio and thermostability as the two other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

1981
1981
1990
1990

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 21 publications
1
28
0
Order By: Relevance
“…Extra flies from each habitat were typed for Adh genotypes (see below) and these data are included in Adh genotypes were scored after electrophoresis of single fly extracts on cellulose acetate membranes using the method described by Lewis and Gibson (1978). The frequency of a third allele Adh FC hD was also scored in the flies collected in 1981 and 1982 using the technique of Wilks et al (1980). However, its frequency was always found to be less than 5 per cent in these populations and it was not scored in the ethanol tolerance experiments or in the single fly assays.…”
Section: And Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Extra flies from each habitat were typed for Adh genotypes (see below) and these data are included in Adh genotypes were scored after electrophoresis of single fly extracts on cellulose acetate membranes using the method described by Lewis and Gibson (1978). The frequency of a third allele Adh FC hD was also scored in the flies collected in 1981 and 1982 using the technique of Wilks et al (1980). However, its frequency was always found to be less than 5 per cent in these populations and it was not scored in the ethanol tolerance experiments or in the single fly assays.…”
Section: And Methodsmentioning
confidence: 99%
“…Buffer was added to the frozen fly in proportion to its weight (200 j.l/mg). The samples were centrifuged at 10,000 g for 3 mins and the supernatant was assayed for ADH (Gibson et a!., 1980). The pellet was used to prepare a sample for the electrophoretic determination of the fly's Adh genotype.…”
Section: And Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All experiments reported here were carried out with crude extracts of 7-day-old adult male flies (10 mg live weight per millilitre of buffer) prepared according to Gibson et al (1980).…”
Section: Melanogaster Stocks and The Preparation Of Enzyme Extractsmentioning
confidence: 99%
“…These thermostable variants were first found in a laboratory stock (Thong et a!., 1975) and subsequently at low but polymorphic frequencies in natural populations in North America (Milkman, 1976;Sampsell, 1977), Australia (Lewis and Gibson, 1978;, the Canary Islands (Hernandez et a!., 1986) and China (Jiang et a!., 1989). Comparisons of other biochemical properties of the Adh thermostability variants with those of ADH-S and ADH-F have shown that the thermostable variants tend to be intermediate with respect to the amounts of ADH protein and they have a secondary alcohol/ primary alcohol activity ratio characteristic of ADH-S rather than ADH-F (Lewis and Gibson, 1978;Gibson et al, 1980;Chambers et a!., 1981b;Gibson etal., 1982b;Sampsell and Steward, 1983;Jiang et a!., 1989). Chambers eta!.…”
Section: Introductionmentioning
confidence: 99%